Kajian Orientalis terhadap Teks dan Sejarah Al-Qur'an Tanggapan Sarjana Muslim - Mohammad Khoeron (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
Besides being studied by the muslims, the Quran is also studied by many of non-Muslim people better known as the orientaslists. Among the big themes of slam being studied by the orientalists is the problem of the text and the history of the Qur’an. The orientalists criticize the validity of the Qur’an through the study of text analysis and history of the Qur’an. They question the authenticy of the Qur’an as being revealed by God. By this writing, the writer tries to catch the response and the reaction of Islamic society through two contradicted thoughts of the big muslim thinkers, namely Fazlur Rahman and A’zami. The writer concludes that study of the Qur’an in the internal milleu of muslim community should also be done scientifically and responsibly by combining the patterns of both Fazlur Rahman and A’zami analysis.